Decoding the mysteries of prostate cancer via cutting-edge liquid biopsy-based urine exosomes profiling - Swarup Sonar (The Journal of Liquid Biopsy)
Exosomes, a subset of extracellular vesicles (EVs), have emerged as crucial players in prostate cancer (PCa) diagnosis. It is involved in cell-to-cell communication. Exosomes cargo based tumor microenvironment (TME) cellular communication is a secret of cancer development and progression. PCa, the second most common cancer in men, holds early diagnostic challenges due to a lack of specific biomarkers. Recent studies have found that tumor-derived exosomes (TEXs) contribute to PCa progression by facilitating immune suppression, angiogenesis, and metastasis. These exosomes, detectable in serum, plasma, and urine, carry diagnostic biomarkers such as specific miRNAs and proteins. Urine-derived exosomes, with their distinct miRNAs, provide a non-invasive diagnostic tool. This method becomes cutting-edge liquid biopsy in PCa. Advanced techniques, such as including AI and nanoplatform-based sensors, improve the precision of exosome-based PCa diagnostics, offering enhanced detection and better treatment outcomes.